MANAGING WASTE LEVEL OF FRESH FOOD MATERIALS: A CASE STUDY OF FAST FOOD RESTAURANT IN BANDUNG - Uli Brenda, Shinta
Restaurant X is a restaurant located in Bandung. It is well known as one of the branches of a very famous fast food brand. This fast food brand has many branches all over the world. Today, people call this type of restaurant as a franchise restaurant, which every branch is owned by different person. As a restaurant, Restaurant X processes the fresh materials into food and beverage, which will be enjoyed by the guests. In order to keep up their customer’s trust, Restaurant X prioritizes the freshness of the food material. The freshness of the food materials will affect the taste of the finished dish. Therefore, the quality of fresh materials will also define the quality of the dish that they want to serve to the customers. Based on that statement, that means Restaurant X has to keep the quality of each fresh food material to create a good dish.